2008
DOI: 10.3892/or.19.5.1205
|View full text |Cite
|
Sign up to set email alerts
|

Lovastatin enhances the antitumoral and apoptotic activity of doxorubicin in murine tumor models

Abstract: Abstract. Despite its effectiveness as an antineoplastic drug, doxorubicin (DOX) is usually associated with cardiotoxicity. Lovastatin (LOV), a hypolipidemic agent used in the clinic, has been demonstrated to have antitumoral and antimetastatic effects in murine models. Since the two agents arrest tumor cells in different phases of the cell cycle and induce apoptosis, the goal of this study was to examine the efficacy of a combination therapy with LOV and low doses of DOX, in an attempt to obtain an improved a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 27 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…If lovastatin is coadministered with P‐gp substrates, there exists the possibility that inhibiting the physiological function of P‐gp may result in decreased elimination of the substrate, requiring dose reduction. However, lovastatin and doxorubicin have been coadministered in mice with no noted adverse toxicity 57, 58. Further evaluation of lovastatin in combination with chemotherapeutic agents that are P‐gp substrates for the treatment of MDR tumors is therefore warranted to examine whether the therapeutic potentiation observed in cell culture models is replicated in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…If lovastatin is coadministered with P‐gp substrates, there exists the possibility that inhibiting the physiological function of P‐gp may result in decreased elimination of the substrate, requiring dose reduction. However, lovastatin and doxorubicin have been coadministered in mice with no noted adverse toxicity 57, 58. Further evaluation of lovastatin in combination with chemotherapeutic agents that are P‐gp substrates for the treatment of MDR tumors is therefore warranted to examine whether the therapeutic potentiation observed in cell culture models is replicated in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…In a study using rat B-cell lymphoma cells, Rozados et al demonstrated that low doses of lovastatin as a single agent decreased tumor cell viability in vitro. Notably, use of lovastatin in combination with doxorubicin induced a significant increase in cytotoxicity when compared to the effect of each agent given alone [90].…”
Section: Doxorubicinmentioning
confidence: 99%
“…Statins were able to potentiate the antitumor effects of anthracyclines in both cellular and animal models. In mice, lovastatin synergistically potentiated doxorubicin-induced cytotoxicity in colon and breast carcinoma (Feleszko et al, 2000;Rozados et al, 2008) and showed an additive effect in lung cancer cell lines (Feleszko et al, 2000). Similar synergistic effects with different anthracyclines were also found for simvastatin and fluvastatin in human rhabdomyosarcoma cells (Werner et al, 2004) and breast cancer cell lines (Budman et al, 2007), respectively.…”
Section: Statins In Cancer Treatmentmentioning
confidence: 99%